(3ebGeGJ MQjQis - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s
(3ChdgG (B:s
(3Gddge CfG fMeOc Ydi eG CSHdJ hHYO aEfg hcHQJ ai gPG GdYWQ QjMg PcQ GdebGeGJ GdJi GHJOYgG HOjY GdReGf s
(3BNQgG (B:s
(3hjNWi HGdYah Efg gh Cgd GdJbhi hCgd GdeZaQI hdi GdNjQGJ ai GdOfjG hGdCNQI Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdfSNI HgG MhGTs
(3Ydjg MGTjI hgh cJGH CWhGb GdPgHs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GdCOHs